Stakeholders’ perspectives on the status of family planning integration into differentiated antiretroviral therapy service delivery models in Uganda: A qualitative assessment - Joseph K. B. Matovu; Martha Akulume; Fredrick Makumbi; Elena Lebetkin; Rhobbinah Ssempebwa; Patrick Komakech; Dieudonne Bidashimwa; Maria Carrasco; Rhoda K. Wanyenze (PLoS ONE, 2025)
Introduction Facility- and community-based differentiated antiretroviral therapy service delivery models (DSDM) for stable patients can offer a convenient platform for integrating self-care-oriented family planning (FP) services into HIV care. However, little evidence exists on the status of FP integration within self-care-oriented DSDM (SC-DSDM). We explored the status of FP integration into SC-DSDM, stakeholders’ perspectives about and barriers to integrating FP into SC-DSDM and suggestions for improving FP integration into SC-DSDM. Methods This qualitative study was conducted in 18 purposely-selected health facilities in 17 districts across four high HIV-prevalence regions between September and October 2022. We conducted 36 in-depth interviews with women living with HIV (i.e., clients), receiving ARV drug refills through SC-DSDM, and 47 key informant interviews with selected stakeholders including healthcare providers, district health managers, implementing partner representatives and policymakers. Data were collected on the different forms of FP integration into SC-DSDM; perspectives on integrating FP into SC-DSDM, and barriers to and suggestions for improving FP integration into SC-DSDM. Data were analyzed following a thematic framework approach. Results We found two forms of FP integration into SC-DSDM: a) one-stop center (in which ART and FP services were provided at the same service delivery point) and b) collaboration/referral to another service delivery point. Only four health facilities offered ART and FP services through the one-stop center; the rest of the health facilities referred clients to the maternal and child health/FP clinic or to other health facilities. All categories of stakeholders agreed that the one-stop center is more convenient and less time-consuming since referral to another service delivery point can increase patient waiting time or result in multiple clinic visits if ART and FP services are offered on separate days. Staff shortages, stock-outs of short-term FP supplies, shortage of adequate office space and lack of integrated registers continue to hamper effective integration of FP into SC-DSDM. Conclusion Despite the potential benefits of FP-HIV integration, FP and ART services continue to be offered as stand-alone programs with limited FP integration into SC-DSDM. These findings call for policy guidance from the Ministry of Health in integrating FP into SC-DSDM in Uganda.